Regulation of iron homeostasis: lessons from mouse models - Altamura, Sandro; Marques, Oriana; Colucci, Silvia; Mertens, Christina; Alikhanyan, Kristina; Muckenthaler, Martina (Molecular aspects of medicine, 2020)
Iron is an essential micronutrient and a critical cofactor for proteins involved in fundamental processes such as oxygen transport, energy production and DNA synthesis. However, iron levels need to be tightly balanced to avoid pathological consequences of iron overload or deficiency. Genetically engineered mouse models with alterations in systemic or cellular iron handling advanced our knowledge how systemic and cellular iron homeostasis is maintained. Here, we prepared a comprehensive overview of mouse models that provide insight into mechanisms of iron regulation and/or rare or frequent iron-related disorders.
Gesehen am 25.11.2020